Handbook of European intelligence cultures - Locke, Chelsea; Nyce, James M.; Graaff, Bob de (Security and professional intelligence education series, 2016)
National intelligence cultures are shaped by their country's history and environment. They examine the environment in which an organization operates, its actors, and cultural and ideological climate, to cover both the external and internal factors that influence a nation's intelligence community.